DIABETIC FOOT: A SCOPING REVIEW OF NEUROSENSORIC DISORDERS – THERMOGRAPHY - Lenny Nurhandayani; Sri Andarini; Heri Kristianto (Jurnal Health Sains, 2023)
Background: Diabetic foot is a chronic complication that can be detrimental and has an impact on the quality of life of diabetic patients. Neurosensory examination of skin temperature using a thermograph can help prevent diabetic foot. Objective: to identify the neurosensory examination of skin temperature using infrared thermographs in addressing the risk of diabetic foot Design: The design in this study is Scoping review Methods: A journal search was conducted using the keywords "infrared thermography, screening or assessment, diabetic foot, and meta-analysis" to collect relevant articles published in the last ten years from four databases (ProQuest, PubMed, ScienceDirect, and Google Scholar). The inclusion criteria were: nurses, patients, diabetic foot, assessment, full-text articles, studies focusing on nursing issues, and written in English. Four journal articles were selected and analyzed using PICO. Results: Four meta-analysis articles on neurosensory examination of skin temperature sensitivity using a thermograph have a p value < 0.05, which can support clinical nursing for monitoring diabetic foot prevention. Conclusion: Examination of skin temperature sensation using a thermograph can be used as a method for neurosensory assessment in monitoring nursing care for structural integrity problems in the physiological changes of the diabetic foot.